Masterplan Kawasan Agrowisata Desa Talun Ponorogo - Sugiarto, Sugiarto; Sutopo, Dhanny Septimawan; Nugroho, Arief Budi; Iriany, Atiek; Subagiyo, Aris (Universitas Nusantara PGRI Kediri, 2025)
Ngebel Lake is one of the leading tourist destinations in Ponorogo Regency. Various annual events are held at Telaga Ngebel to attract local, domestic and international tourist visits. Ngebel Lake has an area of ​​±150 ha which is surrounded by Ngebel Village, Sahang Village, Wagir Lor Village, and Gondowido Village. Talun Village has an area of ​​16.72 km2 or around 27.42% of the entire area of ​​Ngebel District. Talun Village has large potential natural resources and human resources, but has not been utilized optimally. Some of the superior potential of Talun village include the Widodaren waterfall, the Argokiloso hermitage site, Sedayu coffee plantations, village-owned plantation land and a forestry area of ​​around 50 ha, opium coffee, 24 groups of goat and sheep breeders. This agrotourism area has the potential to complement the Telaga Ngebel tourist destination which is already well known to the wider community. This agrotourism area is expected to be able to encourage village economic growth which will lead to improving the welfare of the people of Talun village. The problem is that Talun village does not yet have a master plan for an agrotourism area as part of the gradual development process. Based on these problems, a master plan design for the Talun Village agrotourism area needs to be created.